Use of commercial fungal inoculants for the control of Nacobbus celatus - Lax, Paola (2021)
Several species of plant-parasitic nematodes are responsible for causing considerable damage in agriculture. In Argentina, Nacobbus celatus (previously identified as N. aberrans) is widely distributed. It is a polyphagous species and produces galls on the host roots. In the last years, the search for biological control alternatives to replace chemical nematicides has increased, with emphasis on the use of rhizospheric organisms, including arbuscular mycorrhizal fungi (AMF) and Trichoderma spp. AMF establish a symbiotic association with 80% of terrestrial plants, conferring direct benefits, such as the absorption of nutrients (mainly phosphorus). On the other hand, AMF provide protection against soil pathogens, including plant-parasitic nematodes; the same antagonistic effect is also observed with Trichoderma spp. Commercial inocula of both microorganisms are available on the market, but their efficiency on local nematode populations is unknown. Considering a nematode population, an experiment was performed on tomato plants by applying two commercial inocula at the recommended doses: Rhizophagus intraradices (1 cc) and T. atroviride (dosis 2x106/ml). Treatments were: control, nematode, nematode + AMF, nematode + T. atroviride, nematode + AMF + T. atroviride. Inoculations were carried out at transplanting. Each treatment had five replicates; plants were grown under controlled conditions in a greenhouse for 60 days. After this time, the number of root galls induced by the nematode was counted. In comparison with the control, individual application of AMF and T. atroviride significantly reduced galls by 76% and 43%, respectively. The combined inoculation of the two fungi decreased the number of galls by 48%. The results show that the two commercial inocula have the potential to reduce N. celatus damage. Since the AMF-T. atroviride combination showed to be less efficient than the individual application of AMF, a possible antagonist effect of T. atroviride on AMF remains to be analysed.